Factor that influence customer acceptance toward using biometric as an identity authentication at ATM - Ngah Yusop, Nur Alisa Nadiah; Hassan, Mohamad Ghozali (Universiti Utara Malaysia, 2020)
The increasing crime case that involve ATM such as losing money and identity theft make a lot of people worry especially customer and financial organization. To overcome this issue, a new security system like biometric need to propose. Therefore, the objective of this study is to know the factor that influence customer acceptance using biometric as identity authentication at ATM in Universiti Utara Malaysia. The second objective is to know how much respondent knowledge about biometric. A total of 120 respondents participate in this study and the data is analysed using SPSS. The findings indicate that all the variable has a positive relationship toward the user acceptance. It is recommended to use another factor in Technology Acceptance Model (TAM) to get more accurate factor that influence user acceptance.